BIN1 favors the spreading of Tau via extracellular vesicles - Andrea Crotti; Hameetha Rajamohamend Sait; Kathleen M. McAvoy; Karol Estrada; Ayla Ergün; Suzanne Szak; Galina Marsh; Luke Jandreski; Michael Peterson; Taylor L. Reynolds; Isin Dalkilic-Liddle; Andrew Cameron; et al. (2019)
Abstract Despite Bridging INtegrator 1 ( BIN1 ) being the second most statistically-significant locus associated to Late Onset Alzheimer’s Disease, its role in disease pathogenesis remains to be clarified. As reports suggest a link between BIN1, Tau and extracellular vesicles, we investigated whether BIN1 could affect Tau spreading via exosomes secretion. We observed that BIN1-associated Tau-containing extracellular vesicles purified from cerebrospinal fluid of AD-affected individuals are seeding-competent. We showed that BIN1 over-expression promotes the release of Tau via extracellular vesicles in vitro as well as exacerbation of Tau pathology in vivo in PS19 mice. Genetic deletion of Bin1 from microglia resulted in reduction of Tau secretion via extracellular vesicles in vitro , and in decrease of Tau spreading in vivo in male, but not female, mice, in the context of PS19 background. Interestingly, ablation of Bin1 in microglia of male mice resulted in significant reduction in the expression of heat-shock proteins, previously implicated in Tau proteostasis. These observations suggest that BIN1 could contribute to the progression of AD-related Tau pathology by altering Tau clearance and promoting release of Tau-enriched extracellular vesicles by microglia.